Procopius on soldiers and military institutions in the sixth-century Roman Empire - Whately, Conor (History of warfare, 2021)
"In Procopius on Soldiers and Military Institutions in the Sixth-Century Roman Empire, Conor Whately examines Procopius' coverage of rank-andfile soldiers in his three works, the Wars, Buildings, and Secret History. By evaluating his accounts alongside other comparative evidence, such as the edicts of Anastasius, legislation from the Codex Justinianus, and various papyri, Whately reveals the limitations to Procopius' work, especially when it comes to frontier soldiers. However, this study also shows the impact of Procopius' experiences with institutional matters such as unit structures on his writing, and the particular value he brings to our understanding of recruitment in the sixth century ce"--